2018
DOI: 10.1155/2018/7187284
|View full text |Cite
|
Sign up to set email alerts
|

Medication Noncompliance among Patients with Chronic Diseases Attending a Primary Health Facility in a Periurban District in Ghana

Abstract: Background Despite the growing interest in understanding the aetiology of chronic diseases, limited studies exist on medication noncompliance, especially, among periurban and rural dwellers in Ghana. In this study, we determined the prevalence of medication noncompliance and explored the medication intake behaviour of patients with chronic diseases. The relative influence of cost on medication noncompliance and the risk factors for noncompliance were also assessed. Methods The design was a cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Our study showed that multiple-medication issues had a significant positive association with poor MUSE and medication nonadherence. A recent study by Addo et al74 supports our findings, but another study by Grant et al does not support this association 75. This study found no association with the number of medications, even though the majority of patients took more than three types of medication.…”
Section: Discussioncontrasting
confidence: 48%
“…Our study showed that multiple-medication issues had a significant positive association with poor MUSE and medication nonadherence. A recent study by Addo et al74 supports our findings, but another study by Grant et al does not support this association 75. This study found no association with the number of medications, even though the majority of patients took more than three types of medication.…”
Section: Discussioncontrasting
confidence: 48%
“…Non-compliance to prescribed medications is a remarkably common human experience (Malla, Joober & Garcia 2015 :147–150). This behaviour and its impact on the family system, as well as disease management are magnified in chronic illnesses in psychiatric patients (Addo, Sencherey & Babayara 2018 :1–10). For people with mental illnesses, non-compliance to psychiatric medication extensively adds to the burden of disease and leads to poorer long-term outcomes in these conditions (Alpak et al 2015 :151–156).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports note that the use of herbal preparation for the management of ailments including ACVD is widespread in Ghana due to their perceived accessibility, affordability and perceived efficacy as compared to orthodox medicine 41‐44 . Others cite the inadequate number of health facilities coupled with the limited availability of trained personnel 45,46 . There are also reports that herbal medicine use is on the ascendency due to pressure from peers, family and relatives 25 …”
Section: Introductionmentioning
confidence: 99%